The right of redress - Gold, Andrew S., 1973- (Oxford : Oxford University Press, 2020)
'The Right of Redress' advances the discussion of corrective justice in private law by refocusing the reversal of transactions away from the prevailing account of the wrongdoer's remedial duty and toward the right of an individual to obtain redress, what the author terms 'redressive justice'.
This edition previously issued in print: 2020.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on October 14, 2020).
Keywords: Remedies (Law)